The enhancement of students’ ability in problem solving and mathematical disposition aspect through brain-based learning model - Martyaningrum, Ika Deavy; Dewi, Nuriana Rachmani; Wuryanto, Wuryanto (Unnes Journal of Mathematics Education, 2018)
The main purpose of this research is to analyze the achievement and the increasing of students’ problem solving ability and students’ mathematical disposition as the result of learning application through Brain-Based Learning model and conventional learning comprehensively. This research uses the mix method with concurrent triangulation. The research results show that: (1) The students’ ability of problem solving using Brain-Based Learning model reaches classical learning mastery, (2) the students’ achievement of problem solving using Brain-Based Learning model is higher than that of using conventional learning, (3) the students’ enhancement of mathematical disposition using Brain-Based Learning model is the same with the achievement of using conventional leaning, (4) there is a few correlations between the achievement of problem solving ability and mathematical disposition, as well as their enhancement. To get comprehensive and accurate representation about the enhancement of mathematical disposition through Brain-Based Learning, it is necessary to conduct the future similar study with the same objects yet longer duration.